Discontinuation of opioid agonist treatment following release from prison in a cohort of men who injected drugs prior to imprisonment in Victoria, Australia: A discrete-time survival analysis. (1st January 2023) - Curtis, Michael; Dietze, Paul; Wilkinson, Anna L.; Agius, Paul A.; Stewart, Ashleigh C.; Cossar, Reece D.; Butler, Tony; Walker, Shelley; Kirwan, Amy; Winter, Rebecca J.; Stoové, Mark
Abstract: Background: Retention in opioid agonist treatment (OAT) following release from prison is associated with improved outcomes, however factors associated with post-release OAT discontinuation in Australia are poorly understood. We examined post-release OAT discontinuation in a cohort of men who engaged in approximately monthly injecting drug use (IDU) prior to imprisonment in Victoria, Australia. Methods: Longitudinal data were used to calculate incidence of first-event post-release OAT discontinuation among men released from prison receiving OAT, and single-event discrete-time survival methods were used to estimate associations with post-release OAT discontinuation. Results: Among 110 participants, 55 OAT discontinuations were observed in the two years post-release, an overall crude incidence rate (IR) of 46 per 100 person-years (PY) (95 % confidence interval [95 %CI]: 36–60 per 100PY). Incidence was greatest between release from prison and first follow-up (IR: 84 per 100PY, 95 %CI: 62–116 per 100PY). Initiating OAT during index imprisonment (versus transitioning from community OAT; adjusted hazard rate [AHR]: 2.17, 95 %CI: 1.14–4.13) and identifying as Aboriginal and/or Torres Strait Islander (AHR: 4.95, 95 %CI: 2.00–12.25) were associated with an increased hazard of OAT discontinuation. Conclusion: In a cohort of men with recent histories of IDU released from prison receiving OAT, half reported OAT discontinuation within two years of release from prison, with incidence of discontinuation greatest soon after prison-release. Targeted support for men who initiate OAT during episodes of imprisonment and Aboriginal and/or Torres Strait Islander peoples is necessary to reduce incidence of OAT discontinuation among people at greatest risk of discontinuation. Highlights: We studied opioid agonist treatment (OAT) discontinuation among men exiting prison. Half of participants discontinued OAT within two years of release. Incidence of OAT discontinuation was greatest in the first observation period. Targeted support to at-risk groups may reduce post-release discontinuation.